1-2x(5+x)=7

Simple and best practice solution for 1-2x(5+x)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-2x(5+x)=7 equation:


Simplifying
1 + -2x(5 + x) = 7
1 + (5 * -2x + x * -2x) = 7
1 + (-10x + -2x2) = 7

Solving
1 + -10x + -2x2 = 7

Solving for variable 'x'.

Reorder the terms:
1 + -7 + -10x + -2x2 = 7 + -7

Combine like terms: 1 + -7 = -6
-6 + -10x + -2x2 = 7 + -7

Combine like terms: 7 + -7 = 0
-6 + -10x + -2x2 = 0

Factor out the Greatest Common Factor (GCF), '-2'.
-2(3 + 5x + x2) = 0

Ignore the factor -2.

Subproblem 1

Set the factor '(3 + 5x + x2)' equal to zero and attempt to solve: Simplifying 3 + 5x + x2 = 0 Solving 3 + 5x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-3' to each side of the equation. 3 + 5x + -3 + x2 = 0 + -3 Reorder the terms: 3 + -3 + 5x + x2 = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5x + x2 = 0 + -3 5x + x2 = 0 + -3 Combine like terms: 0 + -3 = -3 5x + x2 = -3 The x term is 5x. Take half its coefficient (2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. 5x + 6.25 + x2 = -3 + 6.25 Reorder the terms: 6.25 + 5x + x2 = -3 + 6.25 Combine like terms: -3 + 6.25 = 3.25 6.25 + 5x + x2 = 3.25 Factor a perfect square on the left side: (x + 2.5)(x + 2.5) = 3.25 Calculate the square root of the right side: 1.802775638 Break this problem into two subproblems by setting (x + 2.5) equal to 1.802775638 and -1.802775638.

Subproblem 1

x + 2.5 = 1.802775638 Simplifying x + 2.5 = 1.802775638 Reorder the terms: 2.5 + x = 1.802775638 Solving 2.5 + x = 1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = 1.802775638 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = 1.802775638 + -2.5 x = 1.802775638 + -2.5 Combine like terms: 1.802775638 + -2.5 = -0.697224362 x = -0.697224362 Simplifying x = -0.697224362

Subproblem 2

x + 2.5 = -1.802775638 Simplifying x + 2.5 = -1.802775638 Reorder the terms: 2.5 + x = -1.802775638 Solving 2.5 + x = -1.802775638 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.5' to each side of the equation. 2.5 + -2.5 + x = -1.802775638 + -2.5 Combine like terms: 2.5 + -2.5 = 0.0 0.0 + x = -1.802775638 + -2.5 x = -1.802775638 + -2.5 Combine like terms: -1.802775638 + -2.5 = -4.302775638 x = -4.302775638 Simplifying x = -4.302775638

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.697224362, -4.302775638}

Solution

x = {-0.697224362, -4.302775638}

See similar equations:

| (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 | | 2b-7=21 | | h+5h-3-6h=0 | | 3-3n=-27 | | 10-8y+(-13)+12y+8-6y= | | 8(-8)+7y=56 | | 2(2x-6)+2(x+3)=24 | | 12m+9-2m-16=0 | | x+2=-34+5x | | 230=2(3x-5)+2(5x+8) | | 100(4+x)=.75(8+x) | | 59+x=59 | | 7x+2=4x+29 | | 6a+10b-a+b= | | 7=-3x+5x-1 | | 6b+3=45 | | (3x-y)(x+2y)= | | X+51=50 | | 2m+4m-m=75 | | 3+10x+3x^2=0 | | 50=6y+32 | | 57+x=85 | | 24x-8=8(3x-1) | | x^4-4x^3-2x^2-4x+1=0 | | 200x+30000=200 | | 4x(5x+2)=0 | | -4x-8+x=-8 |

Equations solver categories